Trinuclear Oxovanadium Complexes of Doxycycline: Synthesis, Characterization and Antiplasmodial Studies - Obaleye, Joshua A.; Abosede, Olufunso O. (International Journal of Environment, Agriculture and Biotechnology, 2019)
Variable oxidation states of vanadium and strong binding ability of doxycycline have been exploited to synthesize three new oxovanadium complexes of doxycycline. The structures of the new complexes were validated by elemental analysis (C, H, N) and FTIR spectroscopy. The ratio of oxovanadium to doxycycline is 1:3 in all the three complexes. Doxycyclinecoordinates tothe first and second vanadium using phenolic oxygen and nitrogen atoms at ring A as well as the amide and keto oxygen atoms of ring A. The third vanadium binds to phenolic and keto oxygen atoms on rings B and C to form complex 1. 2,2-bipyridine and 1,10-phenanthroline coordinate to the third oxovanadium replacing the two aqua ligands attached to it in complexes 2 and 3 respectively. Oxovanadium forms 5-coordinate complexes in all the three complexes.Antiplasmodial studies showed that complex 2 have comparable activity with the parent drug, doxycycline, while all three complexes have higher activities than lincomycin.